Can large carnivores change streams via a trophic cascade?. Issue 1 (11th November 2018) - Beschta, Robert L.; Ripple, William J.
Abstract: Large carnivores were persecuted in Yellowstone National Park, WY, USA, during the late 1800s and early 1900s, leading to extirpation of grey wolves ( Canis lupus ) and cougars ( Puma concolor ). Soon thereafter increased herbivory of riparian plant communities by Rocky Mountain Elk ( Cervus elaphus ) became widespread in the park's northern ungulate winter range or "northern range." Wolves were reintroduced in 1995–1996, again completing the park's large carnivore guild. In 2004 and 2017, we sampled Geyer willow ( Salix geyeriana ), a commonly occurring tall willow, along the West and East Forks of Blacktail Deer Creek in the central portion of the northern range. Results indicated high levels of elk herbivory in the 1990s, as in previous decades, not only continued to keep willows short, generally ≤52 cm in height, but also resulted in stream widening and incision, leading to "oversized" channel cross‐sections and a drastically reduced frequency of overbank flows. However, by 2017, willow heights ≥200 cm ( x ¯  = 310 cm) were prevalent, and canopy cover over the stream, essentially absent in 1995, had increased to 43% and 93% along the West Fork and East Fork, respectively. These recent increases in tall willow heights, greater canopy cover, well‐vegetated streambanks, and the recent development of an inset floodplain all pointed towards a riparian/aquatic ecosystem beginning to recover. Overall, results were consistent with a landscape‐scale trophic cascade, whereby reintroduced wolves, operating in concert with other large carnivores, appear to have sufficiently reduced elk herbivory in riparian areas to initiate the recovery of Blacktail Deer Creek's riparian plant communities and stream channels.